2017
DOI: 10.1093/jbcr/irx044
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Abnormalities Following NexoBrid Use: A Case Report

Abstract: Patients with major burn injury undergo a series of pathophysiologic changes that begin with a systemic inflammatory response and coagulation abnormalities, similar to those experienced by patients with sepsis or severe trauma. Coagulation changes in patients with burns are generally characterized by procoagulant abnormalities, but alterations in fibrinolysis and anticoagulation factors have also been observed. Around 40% of patients with major burn show changes on standard coagulation tests, and these have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…Although other side effects apart from fever after application of enzymatic debridement have been reported in a single case report [14] the present study did not reveal any relevant adverse events after application, irrespective of the burn area.…”
Section: Discussioncontrasting
confidence: 74%
“…Although other side effects apart from fever after application of enzymatic debridement have been reported in a single case report [14] the present study did not reveal any relevant adverse events after application, irrespective of the burn area.…”
Section: Discussioncontrasting
confidence: 74%
“…The enzyme bromelain has been associated with coagulation abnormalities in in vitro and in vivo experiments, as well as after oral medication [104][105][106][107]. A case report of Martìn et al has already drawn attention to this subject in case of topical ED using a bromelain-based approach in burn injuries [108]. When performing ED, it can be recommended to critically evaluate the inclusion of patients with pre-existing risk factors for coagulation abnormalities such as established anticoagulant therapy, low platelet count, or an increased risk of active bleeding (e.g., due to sepsis or gastrointestinal haemorrhage).…”
Section: Results and Advantagesmentioning
confidence: 99%
“…11 This guidance arose from in vitro and animal studies, in which orally administered bromelain was found to reduce platelet aggregation and plasma fibrinogen concentration and to increase prothrombin and partial thromboplastin times. 10 However, it remains unclear whether topical application has similar effects. Martin et al 10 published a case of coagulopathy that occurred shortly after Nexobrid® use, with no reported bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…9 The effects of enzymatic debridement upon coagulation are less clear. Martin et al 10 documented a case of marginally raised clotting times (prothrombin and activated partial thromboplastin ratio), 24 hours after application of Nexobrid® (6% total body surface area (TBSA) treated). There were no signs of active bleeding at that time and the significance of this finding is uncertain, as no other comparable cases have been reported.…”
Section: Introductionmentioning
confidence: 99%